Family Factors as the Primary Determinant of Learning Independence: An Empirical Study of Tiara School Elementary Students - Abdul Canter Sangaji; Doni Koesoema Albertus; Rahmi Rahmi; Vera Maya Santi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the influence of family factors on the learning independence of students at Tiara School Elementary School Jakarta. Family factors analyzed include parental support and attention, grade level, number of children, time spent assisting the child, family income, and parents’ educational attainment. The study employed a quantitative approach using a questionnaire distributed to 55 parents of students from grades 1 to 6. Data were analyzed using multiple linear regression to determine the simultaneous and partial effects of the independent variables on students’ learning independence. The results indicate that parental support and attention and grade level have a significant positive effect on learning independence, while the number of children, time spent assisting the child, family income, and parents’ educational attainment do not have a significant direct effect. The regression model shows that approximately 39.9% of the variation in learning independence can be explained by the family-related variables studied. These findings suggest the importance of active and supportive parental involvement and highlight the developmental differences across grade levels in fostering students’ capacity for self-directed learning. Practically, the study emphasizes the need for schools and parents to collaborate in promoting quality parental engagement that encourages autonomy and self-regulated learning in students.